FOCUS ON COLLABORATIVE LEARNING (Editor: Jeff Golub) - Berner, Audrey (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1989)
Jeff Golub, Editor. FOCUS ON COLLABORATIVE LEARNING. Urbana, IL: National Council of Teachers of English, 1988. 170 pp.